Prototyping emotional design for awareness blog / Darni Mohamed Yusoff - Mohamed Yusoff, Darni (2013)
Emotional design plays a crucial role in the human ability to understand the world, and how they learn new things. Emotional Design will appeal not only to designers and manufacturers but also to managers, psychologists, and general readers who love to think about their stuff. A blog with the emotional design can elicit disappointment, attraction, shame, pride, disgust, awareness, admiration, satisfaction, fear, anger, and any other emotion a person may also experience in response to the interface design of a blog. However, by ignoring the emotional side of interface design would therefore be like denying that these products are designed, bought, and used by humans. This study follows Norman (2004) and Walter (2003) guidelines and learns how to design an emotional design onto the prototype blog. This study also recaps the foundation of a good design, take a look at Norman's three levels of visual design and introduce practical ways to build emotion into a blog. Looking to the phenomenon today, blog is a suitable medium to apply all the emotional guidelines to inject some emotional emotions to the readers. The methodology phases that involved in this project are requirement gathering, requirement analysis, prototype development and documentation. As a result, is a Penyakit Jarang Jumpa Blog with emotional interface design which evokes awareness to the readers is develop. This project will benefit two (2) types of group of people. They are: i. blog designer which the interface guidelines to create a blog with emotional design that have been identified can be a way to provide blog designer in developing a good website/blog with an emotional design and ii. people who need information related to rare diseases.